THE CORRELATION BETWEEN SELF-ESTEEM AND READING COMPREHENSION OF SEVENTH-GRADERS JUNIOR HIGH SCHOOL - Afionita, Devi; Sartika, Dewi; Asmara, Rekha (English Department, University of Riau Kepulauan, Batam,Indonesia, 2024)
This study aimed to investigate the relationship between seventh graders' self-esteem and their reading comprehension skills at SMPN 4 Kayuagung. From a total population of 268 seventh-grade students, 130 participants were selected through purposive sampling. The researchers employed a correlational research design, utilizing a questionnaire and a reading comprehension test for data collection. The self-esteem questionnaire was derived from the established framework of Bagheri and Faghih (2012), ensuring its relevance and accuracy in assessing students' self-perception. To validate the tools, both the questionnaire and the reading comprehension test were piloted with a separate group of students who were not included in the main sample. Data were analyzed using the Pearson Product-Moment correlation. The results revealed a correlation coefficient (r-obtained = 0.778) that was significantly higher than the critical value (r-table = 0.176), with a p-value of 0.000, which is below the 0.05 significance threshold. These findings indicate a strong positive correlation between students' self-esteem and their reading comprehension abilities. This suggests that higher self-esteem is closely associated with better reading comprehension performance, highlighting the critical role self-esteem plays in students' academic success and their ability to process and understand written material. The implication is that self-esteem may influence a student's confidence, motivation, and persistence in academic tasks, which are essential factors in successfully understanding and interpreting texts.